2009
DOI: 10.1001/archinternmed.2009.104
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Malignancies Among HIV-Infected Persons

Abstract: Background As life expectancy of HIV-infected persons increases, cancers have become an important cause of morbidity and mortality. Although cutaneous neoplasms are the most common malignancies in the general population, little data exist among HIV-positive persons especially regarding the impact of HIV-specific factors. Methods We evaluated the incidence rates and factors associated with the development of cutaneous malignancies among HIV-infected persons by examining prospectively collected data from a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 42 publications
6
41
1
3
Order By: Relevance
“…The development of cutaneous NADCs was also showed to be not related to the CD4+ T lymphocites count and receipt of HAART, but HIVinfected subjects are characterized by an high likelihood of developing subsequent cutaneous malignancies at novel sites. In the aforementioned study of Crum-Cianflone et al [82] , 24% of the participants, who initially presented with a BCC, developed a subsequent BCC, and 8% developed a second type of cutaneous cancer.…”
Section: Cutaneous Malignanciesmentioning
confidence: 95%
See 2 more Smart Citations
“…The development of cutaneous NADCs was also showed to be not related to the CD4+ T lymphocites count and receipt of HAART, but HIVinfected subjects are characterized by an high likelihood of developing subsequent cutaneous malignancies at novel sites. In the aforementioned study of Crum-Cianflone et al [82] , 24% of the participants, who initially presented with a BCC, developed a subsequent BCC, and 8% developed a second type of cutaneous cancer.…”
Section: Cutaneous Malignanciesmentioning
confidence: 95%
“…Since the early phase of HIV epidemic, Kaposi sarcoma was the most common malignancy with cutaneous involvement [2] , whereas the incidence and risk factors associated with cutaneous nonADCs (NADCs) among HIVinfected persons are less defined. In a large American cohort of 4490 HIVpositive patients retrieved from 1986 to 2006, there were 254 (5.7%) patients who developed skin cancers, and basal cell carcinoma (BCC) was the most frequent nonADCs, with a ratio of BCC to squamous cell carcinoma (SCC) of 6:1, that differs from transplant recipients who develop SCC in the majority of cases [82] . Similarly in the period between 1985 and 2002 analyzed by an aforementioned Swiss study, BCC were more frequent than SCC, and the overall incidence of nonmelanomatous skin cancer was threefold higher than in the general population (Standardized Incidence Ratio, SIRs = 3.2, 95%CI: 2.24.5) in this large national cohort study [83] .…”
Section: Cutaneous Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Типы ВПЧ высокого риска -16, 18, 31, 35 и 45 -связаны с развитием до 99 % всех карцином шейки матки и аногенитальной области [11]. Начальные по-вреждения эпителия, ассоциированные с этими виру-сами, при определенных условиях могут регрессиро-вать даже без лечения.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified
“…91,95 Thus, the relationship is still unclear among CD4 count, HAART, HIV RNA viral load, and melanoma incidence, as well as disease course. [94][95][96] HIV and Immune Modulation Although the mechanism of HIV's impact on melanoma is still unclear, some evidence suggests the role of immune modulation. Specifically, a 2007 study found a similarity in the pattern of increased cancer risk when evaluating both patients with HIV infection and OTRs.…”
Section: Melanoma In Patients With Hiv Infection/aidsmentioning
confidence: 99%